2023
DOI: 10.1029/2023ms003723
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclones and Equatorial Waves in a Convection‐Permitting Aquaplanet Simulation With Off‐Equatorial SST Maximum

Rosimar Rios‐Berrios,
Christopher A. Davis,
Jonathan Martinez

Abstract: Tropical weather phenomena—including tropical cyclones (TCs) and equatorial waves—are influenced by planetary‐to‐convective‐scale processes; yet, existing data sets and tools can only capture a subset of those processes. This study introduces a convection‐permitting aquaplanet simulation that can be used as a laboratory to study TCs, equatorial waves, and their interactions. The simulation was produced with the Model for Prediction Across Scales‐Atmosphere (MPAS‐A) using a variable resolution mesh with convect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 113 publications
(177 reference statements)
0
2
1
Order By: Relevance
“…In fact, the Atlantic CCKW was not just poorly predicted, but it was hardly represented in the modeling system at all. On the surface, this seems to contrast previous MPAS-A experiments demonstrating good skill in their representation of CCKWs (Judt, 2020;Rios-Berrios et al, 2020, 2022Rios-Berrios, Davis, & Martinez, 2023;Rios-Berrios, Judt, et al, 2023;Weber et al, 2021). However, other CCKWs in our simulations were still well captured, and the IFS system also struggled to capture the same CCKW event (Figure 16).…”
Section: Implications For Cckw Predictabilitycontrasting
confidence: 94%
See 2 more Smart Citations
“…In fact, the Atlantic CCKW was not just poorly predicted, but it was hardly represented in the modeling system at all. On the surface, this seems to contrast previous MPAS-A experiments demonstrating good skill in their representation of CCKWs (Judt, 2020;Rios-Berrios et al, 2020, 2022Rios-Berrios, Davis, & Martinez, 2023;Rios-Berrios, Judt, et al, 2023;Weber et al, 2021). However, other CCKWs in our simulations were still well captured, and the IFS system also struggled to capture the same CCKW event (Figure 16).…”
Section: Implications For Cckw Predictabilitycontrasting
confidence: 94%
“…However, Weber et al (2021) also noted that these 15-km experiments underestimated the amplitude of the wave's rainfall, likely due to an inaccurate linear relationship between moisture and precipitation. Finally, Rios-Berrios, Davis, and Martinez (2023) found that MPAS-A aquaplanet simulations produced realistic CCKW structures at both parameterized and convection-permitting resolutions. The evidence showing that MPAS-A can accurately simulate CCKWs motivates our use of this model for this study.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation